HIV AIDS LITERATUR REVIEW : EFEKTIVITAS PENGGUNAAN METODE WESTERN BLOT TERHADAP DETEKSI ANTI-HIV ANTIBODY - DESTRIA ARDIANA PUTRI (Cendana Medical Journal, 2026)
Western Blot is an analytical technique used to determine protein in a particular sample. One of the biggest arguments in favor of the Western Blot is its sensitivity. Greater sensitivity means that fewer antibodies are required for testing which reduces laboratory costs significantly. The purpose of this study was to analyze the effectiveness of the use of Western Blot on the Detection of Anti-HIV Antibodies. Researchers used the literature review method by entering the keywords hiv, western blot, and hiv antibody detection in the PUBMED search engine. The results of 6 journals were obtained which were then analyzed by researchers.